Hållbart samhällsbyggande genom fysisk planering på detaljplanenivå : Förslag till checklista och fallstudie för ett nytt bostadsområde i Haparanda - Wennberg, Andreas (2015)
Sustainable buildt environment and sustainable development is about creating and designing future society. Community building in the long term and the result of what we do today proves far into the future. Today´s urban development and human way of life and build on the long term is unsustainable. It should therefore be a obvious for all the municipalities, and by all means also all within community building trade, to appear as skilled and responsible actors and that also takes into account environmental and health, when building and planning for sustainable built environment. The future requires a change in community building and ways of life to create a sustainable society. Spatial planning, together with detailed planning, is an important tool to obtain sustainable development.The purpose of this study is to contribute knowledge on how the planning is to contribute to sustainable built environment on the detailed planning level. This in order to meet future needs in a sustainable built environment on the detailed planning level. The goal of the thesis is to show how this can be achieved in the zoning plan/detailed planning, which aspects to think about, to indicate if it contribute/be achieved in the form of a checklist. It is tested in a case study. Then evaluated the usefulness/effect of the checklist and whether it is possible that through a zoning plan/detailed planning to contribute to sustainable development. The study also shows a proposal for how the Granängen, an undeveloped area in Haparanda, how it is planned to live up to a sustainable housing area. The study also evaluates the usefulness/effect of the checklist as well as a zoning plan/detailed planning can contribute to sustainable development. The study serves as a support for the work to manage sustainability in the zoning plan/detailed planning level, the physically-spatial level. Sustainable built environment consists of four interacting factors, social, ecological, economic and physically-spatial sustainability. The results show that for ...